The Effectiveness of Using Sport, Spirituality and Values in Youth Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
From the first days of independence of Uzbekistan, our republic has paid great attention to physical culture and sports. The Republic of Uzbekistan was one of the first among the CIS countries to adopt the resolution "On physical and legal acts". This resolution is about the content of law and the upbringing of a harmonious generation.